The Influence Of Storytelling, Social Media Marketing, and Customer Reviews Of Coffee Roasters On The Purchase Decision Of Single-Origin Arabica Coffee Beans By Coffee Shops - Luqman Anthoni Arethusa; Stefanus Yufra Menahen Taneo (International Journal of Management Research and Economics, 2024)
The coffee industry, centered on Arabica and Robusta beans, relies heavily on coffee shops for delivering quality products, particularly single-origin Arabica coffee. Coffee roasters, operating in the B2B market, supply coffee shops, shaping product quality and customer satisfaction. This study examines the impact of marketing strategies—storytelling, social media, and customer reviews—on coffee shop owners' decisions to purchase Arabica beans. Utilizing a quantitative approach with 222 respondents and multiple linear regression analysis in SPSS, findings show a significant positive influence of these strategies on purchase decisions. Together, they explain 70.6% of the variance, with remaining factors beyond the study's scope. This underscores the crucial role of marketing strategies in shaping coffee purchasing decisions for coffee shops.